A combined SEM and TEM studies of microsporum canis after in vitro treatment with atratoxin B1 from holothuria atra - Darah, I; Teo, M. L; Ibrahim , C. O (Universiti Kebangsaan Malaysia, 1996)
Atratoxin B1 which was extracted from a local sea cucumber, Holothuria atra is a potential antifungal agent against dermatophytes. Exposure of Microsporum canis mycelia inoculated into Sabouraud glucose agar medium to the 10 mg/ml atratoxin B1 solution, resulted in complete suppression of the fungal growth. Prolonged exposure to the atratoxin B] (72 hours) resulted with necrosis in a substantial portion of the existing hyphae. The main anomalies noted were the abnormally shaped hyphae and the alterations in its morphology and cytology.